MISI GEREJA:: MENJANGKAU YANG TIDAK TERJANGKAU DI ERA DAN PASCA PANDEMI COVID-19 - Deflit Dujerslaim Lilo (Phronesis: Jurnal Teologi dan Misi, 2020)
The spread of the Corona virus has an impact on the implementation of the church's mission. The church, which has been carrying out various religious activities physically, is forced to use various digital media so that Christians can still get services. Even so, the virtual church services have not yet reached out to community groups such as Generation Z and those who do not have the capacity to access them. The purpose of this research is to find solutions that churches can do to reach communities that have not been reached by digital church services. Based on the study using the descriptive-analysis method, the authors conclude that church stewardship in social media should not only focus on the aspect of worship but also on discipleship which will mature the faith of believers and in the end, both young and old church members can be involved to help the church develop the ministry during the period of physical distancing even after this period.